Anmeldelser - Kirkegaard, Annemette (Danish Yearbook of Musicology, 2000)
Review of: Peter Reinholdsson: Making Music Together. An Interactionist Perspective on Small-Group Performance in Jazz (Acta Universitatis Upsaliensis, Studia Musicologica Upsaliensia Nova Series 14). Institutionen för Musikvetenskap, Uppsala 1998.